2015
DOI: 10.1039/c5tb00833f
|View full text |Cite
|
Sign up to set email alerts
|

BSA-coated magnetic nanoparticles for improved therapeutic properties

Abstract: In recent years, magnetic nanoparticles have been widely investigated for their potential in biomedical applications. For successful in vivo application, magnetic nanoparticles must satisfy several requirements such as biocompatibility, invisibility to the immune system, high colloidal stability in biological fluids, and long blood circulation times. In this study, we have developed a formulation in which the magnetic nanoparticles are coated with bovine serum albumin to provide enhanced colloidal stability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…Results show that coating with BSA decreases the degradation of the nanoparticles and reduces the toxicity in the animal model [14]. Another study showed that BSA coating of an iron oxide core can improve the in vivo and in vitro therapeutic outcome for efficient cancer treatment [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Results show that coating with BSA decreases the degradation of the nanoparticles and reduces the toxicity in the animal model [14]. Another study showed that BSA coating of an iron oxide core can improve the in vivo and in vitro therapeutic outcome for efficient cancer treatment [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to covalently anchor BSA require the modification of the initial SPIONs with tedious reactions with organic solvents (toxic for biological applications), the exchange of solvents and they restrict and fix the conformation of the anchored protein. 16,21 Non-covalent strategies require hydrophilic iron oxide surfaces, the common method of synthesis cannot offer it; and it adds an extra step. 16,17 In our case, we synthesized SPIONs using microwave-assisted thermal decomposition and capped them with citrate, rendering hydrophilic SPIONs in a single step.…”
Section: Introductionmentioning
confidence: 99%
“…Surface Modifi cation of ZnS:Mn/MnS Core-Shell NRs : To prepare the contrast agent solutions according to previous reports, [ 57,58 ] 10.0 mg of ZnS:Mn/MnS core-shell NRs powder was weighed and transferred into a glass vial. Ethylenediamine (Xiya Reagent) (2 mL) was added into the vial followed by the addition of 0.05 mL of ethanedithiol (J&K).…”
Section: Methodsmentioning
confidence: 99%
“…This demonstrates that the migration of Mn ions into the ZnS NRs for doping occurred prior to the coating of the MnS layer during the synthesis. [ 57,58 ] BSA has been one of the most extensively studied proteins because of its sequence and structural homology to human serum albumin, and it provides NCs with a better hemocompatibility, longer blood circulation times, as well as hindering the undesired adsorption of other proteins. However, the TEM image also shows lots of particles in the product, which were MnS nanoparticles generate by the excess Mn and S sources.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 99%
See 1 more Smart Citation